Sesamol induces cytotoxicity via mitochondrial apoptosis in SCC-25 cells. (December 2021) - Ezhilarasan, D; Ali, D; Varghese, R
Sesamol is the main constituent of sesame seed oil and is obtained from Sesamum indicum . Oral squamous cell carcinoma (OSCC) is one of the most common neoplasms affecting the oral cavity. In this study, we investigated the cytotoxic potentials of sesamol on human oral squamous carcinoma (SCC-25) cells. Human oral squamous carcinoma cells were treated with different concentrations (62.5, 125, and 250 μM/mL) of sesamol for 24 h. Cytotoxicity was analyzed by 3- (4, 5- dimethylthiazol -2- yl) -2, 5-diphenyltetrazolium bromide (MTT) assay. Intracellular reactive oxygen species (ROS) expression was investigated by dichloro-dihydro-fluorescein diacetate assay. Apoptosis-related morphology was analyzed by acridine orange/ethidium bromide staining. Caspase-9 expression was analyzed by confocal microscopic double immunofluorescence staining. Mitochondrial apoptosis-related markers are analyzed using qPCR. Sesamol treatment caused a significant cytotoxic effect in OSCC cells. Sesamol-induced cytotoxic effect was associated with intracellular ROS generation. Sesamol treatments induced a significant increase in the early and late apoptotic cells. This treatment also induced caspase-9 expression in OSCC cells. Sesamol treatments caused downregulation of Harvey rat sarcoma viral oncogene homolog (HRAS) expression at protein and gene levels. Sesamol treatment modulates intrinsic apoptotic marker gene expression in OSCC cells. Overall results confirm the anti-cancer potential of sesamol and it seems to be a promising candidate for OSCC.